Penurunan berat badan setelah 12 minggu latihan beban menggunakan resistance band pada mahasiswa yang mengalami obesitas - Kuswahyudi, Kuswahyudi; Taufik, Muhamad Syamsul; Setiakarnawijaya, Yasep; Hazar, Fatih; Purwoto, Septyaningrum Putri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Obesity among college students poses a significant health concern, as excess weight heightens the risk of various diseases. The study aims to determine the effects of a 12-week resistance band weight training program on weight loss in obese college students. This research employs an experimental method, specifically using a "One Group Pre-Post Test Design." This involves administering a pre-test before the intervention and a post-test after the intervention. The participants in this study are adolescent athletes from the State University of Jakarta. The sample consists of 30 individuals selected through purposive sampling based on specific criteria: students from the State University of Jakarta, aged 16-23 years, both male and female. Data collection involves the experimental group and control group, the participant's BMI before and after the 12-week resistance band training program. BMI measurements were conducted using the OMRON brand BIA (Bioelectrical Impedance Analysis) method. Data analysis was performed using SPSS version 21, which includes the normality prerequisite test and is continued with the independent Sample T-Test. The results of the Independent Sample T-Test showed that the Sig value was 0.000 < 0.05. A 12-week resistance band weight training program has a significant effect on weight loss in obese college students. Therefore, the resistance band strength training model significantly influences weight loss more than traditional training methods. This suggests that resistance band training is highly effective for weight loss in adolescents aged 16-23 years and can be incorporated into physical exercise programs for this age group.